Design of 5G MIMO antenna arrays - Pan Thway Nu Nu (Nanyang Technological University, 2022)
As the usage of electronic devices is rapidly growing at a huge leap, data and signal consumption rates are incredibly competitive and users are struggling to get a good signal, especially in crowded locations. In fact, the internet of things (IoT), Massive-MIMO, smart cities, and other markets are emerging which hugely burden the 5G network. These urge 5G to increase bandwidth and improve system efficiency. Thus, a 5G Multiple Input Multiple Output (MIMO) antenna can be used to counter the challenges. MIMO antenna gives a promising solution because of its higher capacity, higher data rates, and provides quality mobile communication. MIMO technology plays a vital role in 5G technology due to its larger bandwidth. It also radiates power in more than one direction. In this paper, we will design a microstrip patch antenna and make the necessary improvements to enhance the antenna operation. The goal is to design a 5G MIMO antenna for wideband applications. The antenna uses Rogers RO4003C substrate having a dielectric constant of 3.55. The substrate is 1.5mm in height and operates at a 24 GHz center frequency. The MIMO consists of 4×1 linear array configurations. Additional design of a 2x1 linear array with a 28 GHz center frequency is also simulated as part of this project. Simulations of all the designs have been done using CST microwave studio.